Utilization of an Inclined Plane to Increase the Efficiency of Forward Roll on Class IV Students at Paringin 2 State Elementary School - Rusmana, Adi; Rahmadi, Rahmadi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to determine the utilization of an inclined plane to improve the efficiency of the front roll on class IV students at Paringin 2 State Elementary School. The method used in this study was a pre-experiment with a pre-test and post-test research design. The data analysis technique uses the T-Test to compare the average of two samples to test the truth or not of a hypothesis; besides that, the research uses the percentage formula to calculate the percentage of complete students and incomplete students. The research sample was class IV students of Paringin 2 State Elementary School, Balangan Regency, totalling 19 people, and the object of research focused on the utilisation of an inclined plane to increase the efficiency of the front roll movement. The results in pre-test and post-test results showed that the highest score remained at 100. The lowest score was 55.5 in the pre-test and 80.5 in the post-test. The average was 86.8 in the pre-test and 95.3 in the post-test. The Minimum Attainment Criteria was 75. Students who completed 78.95% in the post-test and 100% in the post-test. Students who did not complete the pre-test were 21.05% and the post-test was 0%. The t-test results show P-value = 0.0000239304, far below 0.05, so there is a significant difference in student learning achievement before and after the application of the inclined plane in front roll learning. In conclusion, the utilization of an inclined plane significantly increases the efficiency of the front roll movement in class IV students at Paringin 2 State Elementary School.